Role of Nepafenac 0.1% Ophthalmic Solution in Preventing Intraoperative Miosis during Phacoemulsification: Doi: 10.36351/pjo.v37i1.1038 - Ahmed, Sairam; Ghazanfar, Iqra; Khan Niazi, Fuad Ahmad; Raza, Ali (Pakistan Journal of Ophthalmology, 2020)
Purpose: To compare 0.1% Nepafenac ophthalmic solution with placebo in terms of decreasing mean intraoperative miosis in patients undergoing cataract surgery. Study Design: Quasi experimental study. Place and Duration of Study: Department of Ophthalmology, Holy-Family Hospital Rawalpindi from September 2017 to March 2018. Methods: A total of 150 eyes with senile cataract of patients between 40-80 years of age and of both genders, undergoing uneventful cataract surgery and fulfilling the inclusion criteria were included. Patients were divided into 2 equal groups. Group A received Nepafenac eye drops and group B received placebo drops (Preservative free artificial tears). The diameter of pupil as viewed through the operating microscope was measured with Castroviejo Caliper at following steps; immediately before the start of surgery (baseline), after complete nucleus removal and at the end of surgery. Results: Mean decrease in pupil size from the start of surgery to the end of phacoemulsification in Group A (nepafenac group) was 0.48 ± 0.26 mm while in Group B (placebo group) it was 1.40 ± 0.49 mm (P = 0.0001). Mean decrease in pupil size from start to end in Group A (Nepafenac group) was 0.75 ± 0.32 mm while in Group B (placebo group) was 2.02 ± 0.62 mm (P = 0.0001). Conclusion: Intraoperative miosis in terms of mean decrease in pupils size (both from start of surgery till phacoemulsification and also from start of surgery till end of surgery) was lower in 0.1% Nepafenac group as compared to placebo group. Key Words: Phacoemulsification, Miosis, Nepafenac.